DESIGN AND BUILD LEARNING MEDIA FOR PNEUMATIC AND HYDRAULIC ANIMATION BASED ON ANDROID - Pramastiko, Damar Aji; purnawan, purnawan; Salam, Haipan (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Pneumatic and hydraulic learning media are ussualy used sofware that intergated on a computer device. Android based learning media can be use as an alternative media that can fullfill the limitation of computer based media. This study aims to produce and to determine the feasibility of android based learning animation media in pneumatic and hydraulic subjects, especially pneumatic components. Analysis, Design, Development, Implementation, Evaluation (ADDIE) is used as a research method in producing learning media. The respondend are students of the Department of Mechanical Engineering Education who have passed and are currently contracting pneumatic and hydraulic courses. Judgment of instructional media is carried out by material experts and media experts. The results shows that the android based learning media are feasible to be use in the learning activities with the judgment score from media and subject experts are 89,5% and 94%, respectively. Moreover, student respondends were also give good score with the presentase 84,8%.